The Poetics of Embodiment: Elisaveta Bagryana and Rade Drainac, a Love Affair (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The article aims to disclose how the encounters with Drainac changed Bagryana’s poetry and her perception of poetic language and herself. For that purpose, the poetry of Bagryana before 1930, mainly the key poems from “The Eternal and Holy”, will be analysed. The views expressed in those poetic strophes will be related to Drainac’s own poetic texts from the 1920s and his ideas on aesthetics and writing as expressed in the magazine “Hypnos”. Then the article will proceed to examine Bagryana’s 1930-31 poems and the tangible alteration in her wording, images and poetic rhythm. The final underlying question this article attempts to answer is about the struggle of poetic language to reinvent itself while incorporating and reassembling the poet’s everyday life and encounters within the poems’ structure.
Keywords: Bagriana; Drainac; biography; poetry; influence